Simplified membrane-like systems describing the physical behaviors of cholesterol and anti-diabetic drugs - Trujillo, Alejandro M., author; Crans, Debbie C., advisor; Roess, Deborah A., committee member; Frye, Melinda A., committee member; Van Orden, Alan K., committee member (Colorado State University. Libraries, 2013)
This work evaluates the properties contributing to natural membrane permeability by using simplified systems. Absorption mechanisms are a critical step in evaluating the action of orally active drugs. Reverse micelles (RMs) were used as a membrane-like model to analyze the permeation through spectroscopy. The properties exerted by the ligand and ligand substituents were evaluated in the context of membrane permeation. The polydentate ligand of anti diabetic dipicolinatooxvanadium(V) [VO2dipic])-, 2,6-pyridinedicarboxylate (dipic2-) was observed for permeability in sodium bis(2-ethylhexyl)sulfosuccinate (AOT) RMs. Measurements using proton nuclear magnetic resonance (1H NMR) spectroscopy revealed the permeation and hydrophobic stability at physiological pH for dipic2-. Substituents, NH2, OH, H, Cl, NO2 were evaluated forinfluencing the stability and permeability of [VO2(dipic)]-; in AOT RMs. Using infrared spectroscopy (IR), substituent changes significantly influenced the permeation of the vanadium complex series. Properties contributing to the membrane permeation of drugs may also be altered by membrane composition. Cholesterol is present in intestinal membranes and is known to possess properties reducing permeability. A system composed of cetyltrimethylammonium bromide (CTAB), 1-pentanol, cholesterol, and an aqueous phase formed RMs characterized by NMR and dynamic light scattering (DLS). Cholesterol altered the RM structure and proton transfer rates between the water and 1-pentanol of the system. Combined, this work illustrates that ligands, substituents, and membrane components influence the uptake of orally administered drugs.
Keywords: absorption; anti-diabetic; microemulsion; permeability; reverse micelle; vanadium